Rural use of health service and telemedicine during COVID-19: The role of access and eHealth literacy. (May 2021) - Rush, Kathy L; Seaton, Cherisse; Li, Eric; Oelke, Nelly D; Pesut, Barbara
The COVID-19 pandemic has driven a greater reliance on telemedicine, yet rural access, use, and satisfaction with telemedicine and the role of eHealth literacy are unknown. Using a cross-sectional design, 279 (70.6% female) western rural Canadians completed an online survey. The majority of participants reported access to telemedicine, but nearly 1/5 lacked access to online or virtual mental health services. The majority of participants had used health care services following the declared COVID-19 pandemic in North America, and just under half had used telemedicine. Telemedicine satisfaction scores were higher among participants who had used video ( M = 4.18) compared to those who used phone alone ( M = 3.79) ( p = 0.031). Telemedicine satisfaction and eHealth literacy were correlated ( r = 0.26, p = 0.005). Participants did not want telemedicine to replace in-person consultations. Telemedicine practice requires that rural residents have the resources, ability and willingness to engage with remote care.